Calculation of the 1D grating scattering matrix frequency derivatives. (March 2020) - Shcherbakov, Alexey A.; Pogorelskaya, Lydia Yu.; Bogdanov, Andrey A.
Abstract: In this contribution we develop methods for calculation of complex poles of scattering matrices which are based on analytically found frequency derivatives of these matrices instead of commonly used finite difference derivation. The analysis is made within the framework of the Fourier Modal Method and the analytical scattering matrix method proposed previously. Usage of analytical formulas may improve the accuracy of numerical algorithms based on the matrix Newton and Householder methods.